2015
DOI: 10.1002/fsn3.225
|View full text |Cite
|
Sign up to set email alerts
|

Daily consumption of a mangosteen‐based drink improves in vivo antioxidant and anti‐inflammatory biomarkers in healthy adults: a randomized, double‐blind, placebo‐controlled clinical trial

Abstract: Mangosteen (Garcinia mangostana) is a tropical fruit cultivated mainly in Southeast Asia. Recent studies have shown mangosteen has many health benefits. In this study, we aimed to determine the effects of a mangosteen-based beverage on antioxidant and anti-inflammatory and immunity biomarkers in plasma of healthy adults. A randomized, double-blind, placebo-controlled clinical trial was conducted using 60 participants, 30 men, and 30 women, ages 18–60. Participants were randomly divided into two groups, placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 27 publications
1
53
0
1
Order By: Relevance
“…Additionally, active research should also be directed at novel drug formulation and delivery systems, such as solid dispersion and nanoparticle formulations of α-MG, which would enhance its targeting effect, bioavailability, and efficacy. Anyway, the current available preclinical and mechanistic ▶ Decreased levels of serum CRP levels; enhanced antioxidant capacity; immunity biomarkers IgA, IgG, IgM, C3 and C4 were not affected; no side effects on human hepatic and kidney functions [134] data has indicated that α-MG is a promising candidate to be used in cancer chemoprevention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, active research should also be directed at novel drug formulation and delivery systems, such as solid dispersion and nanoparticle formulations of α-MG, which would enhance its targeting effect, bioavailability, and efficacy. Anyway, the current available preclinical and mechanistic ▶ Decreased levels of serum CRP levels; enhanced antioxidant capacity; immunity biomarkers IgA, IgG, IgM, C3 and C4 were not affected; no side effects on human hepatic and kidney functions [134] data has indicated that α-MG is a promising candidate to be used in cancer chemoprevention.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Chitchumroonchokchai et al [133] revealed the presence of free and conjugated forms of α-MG in plasma and urine after consuming a mangostin-rich mangosteen juice. In a recent randomized, double-blind, placebo-controlled clinical trial, the investigators examined the effects of a mangosteenbased beverage (Verve ® ) on antioxidant, anti-inflammatory, and immunity biomarkers in the plasma of healthy adults [134]. It was found that after the 30-day trial, the CRP level in the group given the mangosteen-based drink formula significantly decreased by 46 %, and that antioxidant capacity in the bloodstream showed 15 % more than that in the placebo group.…”
Section: Molecular Modeling and Docking Studymentioning
confidence: 99%
“…In another study, orally 40 mg/kg α‐mangostin decreased the level of COX‐2 and Il‐6 induced by LPS in mouse brain (Nava Catorce et al, ). Significant elevation in antioxidant capacity in the blood stream and reduced inflammatory markers such as C‐reactive protein by 46% have been shown by daily consumption of a mangosteen‐based drink for 30 day in healthy adult (Xie et al, ). In pilot, dose‐finding study on 122 overweight and obese persons, who take mangosteen juice blend (XanGoJuice™) in high dose (18 oz.…”
Section: Methodsmentioning
confidence: 99%
“…8m Interestingly, isogarcinol ( 1 ) is also available for human consumption in mangosteen drinks and capsules as a remedy for arthritis. 9 Only one total synthesis of 1 has been reported since its isolation in 1980, an elegant strategy accomplished in 15 steps by Pleitker and co-workers. 10,11a The compound has been isolated from numerous sources, 11 and a large scale extraction procedure was developed for its procurement.…”
Section: Introductionmentioning
confidence: 99%